2012
DOI: 10.1093/brain/aws155
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of intracranial pressure correlates with outcome after traumatic brain injury

Abstract: This study applied multiscale entropy analysis to investigate the correlation between the complexity of intracranial pressure waveform and outcome after traumatic brain injury. Intracranial pressure and arterial blood pressure waveforms were low-pass filtered to remove the respiratory and pulse components and then processed using a multiscale entropy algorithm to produce a complexity index. We identified significant differences across groups classified by the Glasgow Outcome Scale in intracranial pressure, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 41 publications
(53 reference statements)
3
69
1
2
Order By: Relevance
“…Recently, several nonlinear analytical methods had been applied to quantify the complex regulatory dynamics of human biological signals such as heart rate variability21, electroencephalography22, and intracranial pressure23. Because the characteristics of those signals are physiologically nonlinear, the advantages of using nonlinear methods vs. conventional linear methods to describe the complex patterns have been shown in several earlierstudies21222324.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several nonlinear analytical methods had been applied to quantify the complex regulatory dynamics of human biological signals such as heart rate variability21, electroencephalography22, and intracranial pressure23. Because the characteristics of those signals are physiologically nonlinear, the advantages of using nonlinear methods vs. conventional linear methods to describe the complex patterns have been shown in several earlierstudies21222324.…”
Section: Discussionmentioning
confidence: 99%
“…MSE has been widely applied in analyzing many physiologic signals, such as heart rate [2,3,24], electroencephalography (EEG) signal [25][26][27], blood oxygen level-dependent signals in functional magnetic resonance imaging [28], diffusion tensor imaging (DTI) of the brain [29], neuronal spiking [30], center of pressure signals in balance [31,32] and intracranial pressure signal [33].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, prior research has been devoted to the development of alternatives to study ICP. Some of them were based on non-linear methods, including approximate entropy [13], multiscale entropy [14] and Lempel-Ziv complexity [8,15]. Results revealed that intracranial hypertension was associated with a lower ICP signal complexity in children with TBI [13,15] and in adults with hydrocephalus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that intracranial hypertension was associated with a lower ICP signal complexity in children with TBI [13,15] and in adults with hydrocephalus [8]. Moreover, reduced complexity seems to be linked to poor outcome after TBI [14]. On the other hand, previous studies addressed the spectral analysis of ICP signals [11,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%